Auction Application for Beringkit Animal Traditional Market Based on Android - I Gede Galang Surya Prabawa; I Nyoman Piarsa; Gusti Agung Ayu Putri (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
Beringkit Animal Market is one of the large traditional animal markets in Bali which is famous for selling superior cows. In addition to selling superior cows, Beringkit Animal Market also sells dogs and various types of poultry such as chickens, ducks and roosters. However, in the midst of the COVID-19 outbreak, traditional markets are considered as the main cluster for the spread of COVID-19 due to the large number of interactions between buyers and traders. The implementation of Community Activity Restrictions (PPKM) has resulted in a lack of income for traders at the Beringkit Animal Market. This study aims to design an Android-based online animal auction application as a medium for buying and selling animals to minimize physical interaction between buyers and traders, the online auction transaction process is chosen because the auction transaction process can bring together traders and buyers in the same online media and make offers up to reach the highest agreed price. The research method applied is the DSRM method or Design Security Research Method, application development uses Android Studio to develop mobile applications, and uses Visual Studio Code to develop web-based systems. Data storage and web server management in this study using MySQL and Laravel. The results of this study are in the form of an Android-based animal auction application that can be used as a medium for transactions between buyers and traders who have gone through the blackbox testing process with the test results as expected.